Non-invasive hemodynamic evaluation following TAVI for severe aortic stenosis. (2nd May 2022) - Grinberg, T; Aviv, Y; Perl, L; Wiessman, M; Kornowski, R; Orvin, K
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Various hemodynamic changes occur following Transcatheter aortic valve implantation (TAVI) that impact treatment decisions. NICaS, a noninvasive whole-body bio-impedance monitoring system to assess hemodynamics and fluid balance, was tested in patients with severe aortic stenosis (AS) before and after TAVI. Methods: Between October 2019 and December 2020 all consecutive patients with severe AS undergoing TAVI were assessed by NICaS at several time points – 24 hours before (baseline) and after the procedure, at hospital discharge and at 30 days to 1 year follow-up. Excluded were patients undergoing TAVI due to reasons other than severe AS, patients under general anesthesia and those who died at the catheterization lab or immediately following the procedure. Results: We performed hemodynamic analysis on 97 consecutive patients who underwent TAVI using either Medtronic Evolut R (54%), Edwards Sapien 3 (32%) or SYMETIS ACURATE neo (13%). Patients were more often women (54%) and had multiple comorbidities including hypertension (83%), dyslipidemia (79%), coronary artery disease (46%), and diabetes mellitus (37%). Compared to baseline NICaS measurements, we observed increases in systolic blood pressure (BP) and total peripheral resistance (TPR) within 24 hours following TAVI (systolic BP 132.5±22.3 mmHg at baseline versus 148.4±23.9 mmHg after TAVI, P<0.001; TPR 1754±520 versus 2094±752 dynes*s/cm5, respectively, P<0.001) while cardiac output (CO), cardiac index (CI) and stroke volume (SV) decreased (CO 4.2±1.2 versus 3.9±1.2 L/min, respectively, P=0.013; SV 62±15 versus 56±15.8 mL, P=0.002). However, opposite trends were demonstrated exclusively in patients with ejection fraction (EF) under 40%. At follow-up (median 59 days, IQR [39.5-91]) these hemodynamic measurements returned to values that were not statistically different from the baseline, despite a significant improvement in EF from baseline to follow-up (55.6±11.6 to 59.4±9.4%, P<0.001). Conclusion: A unique pattern of short and longer term adaptive hemodynamic changes was demonstrated using the NICaS system among patients undergoing TAVI. These findings require validation and further research to their underlying mechanism if NICaS is to be used as a bedside monitoring tool to guide treatment decisions.